2006
DOI: 10.1677/joe.1.06939
|View full text |Cite
|
Sign up to set email alerts
|

Developmental aspects of adipose tissue in GH receptor and prolactin receptor gene disrupted mice: site-specific effects upon proliferation, differentiation and hormone sensitivity

Abstract: Direct metabolic effects of GH on adipose tissue are well established, but effects of prolactin (PRL) have been more controversial. Recent studies have demonstrated PRL receptors on adipocytes and effects of PRL on adipose tissue in vitro. The role of GH in adipocyte proliferation and differentiation is also controversial, since GH stimulates adipocyte differentiation in cell lines, whereas it stimulates proliferation but inhibits differentiation of adipocytes in primary cell culture. Using female gene disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 45 publications
0
34
0
1
Order By: Relevance
“…The degree of GH-deficiency is considered to be important in the regulation of intra-abdominal fat, but there is now growing evidence for differential regulation of specific adipose depots (17,18,34). As reported previously (21), the adiposity in the tibial marrow compartment was not regulated parallel to that in abdominal fat (studies 1 and 3), but the advantage of analyzing marrow fat is that it enables ready discrimination between adipocyte hypertrophy (lipid accumulation) and adipocyte hyperplasia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The degree of GH-deficiency is considered to be important in the regulation of intra-abdominal fat, but there is now growing evidence for differential regulation of specific adipose depots (17,18,34). As reported previously (21), the adiposity in the tibial marrow compartment was not regulated parallel to that in abdominal fat (studies 1 and 3), but the advantage of analyzing marrow fat is that it enables ready discrimination between adipocyte hypertrophy (lipid accumulation) and adipocyte hyperplasia.…”
Section: Discussionmentioning
confidence: 74%
“…In the profoundly GH-deficient lit/lit mouse a significant elevation in total proportionate fat mass (14) is reflected in increased inguinal and retroperitoneal fat, whereas parametrial fat is unaffected (26). In addition, analysis of the adiposity profile in GH receptor-binding protein null (GHR/BP Ϫ/Ϫ )-null mice has revealed that there is a sex-dependent component in this relationship, with fat accretion in GHR/BP Ϫ/Ϫ males being elevated in subcutaneous (subscapular) and retroperitoneal depots, but unchanged in epididymal fat (3,15), whereas parametrial fat is decreased in GHR/BP Ϫ/Ϫ females, with no significant effect on inguinal fat mass (18). Given that the lipolytic action of GH is dependent upon the pattern of tissue exposure (10), it is likely that some of these discrepancies may be related to the disturbance of the underlying pattern of GH secretion in these models.…”
mentioning
confidence: 99%
“…Genetic analysis using knockout and transgenic mice contributed significantly in understanding the role of prolactin in target organ function (Bole-Feysot et al, 1998;Bartke, 1999;Ormany et al, 2003;Flint et al, 2006). Effects in knockout mouse models have been grouped as the reproduction-lactation phenotype, the bone phenotype, and the behavior phenotype (Goffin et al, 1999;Kelly et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas SubQ WAT depots are also disproportionately enlarged in GHA mice at all ages, the marked increase in obesity with advancing age is a result of all WAT depots being relatively enlarged. Notably, female bGH, GHR−/−, and GHA mice show a similar trend as their male counterparts; however, the difference is less significant as seen in males, and the age at which significant differences are seen is somewhat delayed [96,128,135,137]. Depot differences in AT are apparent in these mice.…”
Section: Obesity and Depot-specific Alterations In Gh Mouse Linesmentioning
confidence: 78%